PATTERN, MANAGEMENT AND OUTCOME OF UROLOGICAL COMPLICATIONS IN FIRST POST-TRANSPLANT YEAR IN 50 CASES OF RENAL TRANSPLANT - Suhail, Mohammad Ali; Khaskeli, M. Saleh; Hamza, Ameer (Journal of Ayub Medical College Abbottabad, 2011)
Background: Chronic renal failure needs substitutive treatment such as haemodialysis and peritoneal dialysis for the patients to survive. Kidney transplantation improves survival of patients with chronic renal failure. This study was conducted to identify the pattern, management and outcome of urological complications in first post-transplant year in 50 cases of renal transplant recipients. Methods: This case series study was conducted in the Department of Urology and Transplantation, Mayo Hospital, Lahore, during the period of three years, from Jan 2006 to Dec 2008. All 50 patients were admitted through outdoor department, Dialysis Unit, and directly referred from other hospitals. Donor and recipient were evaluated thoroughly by history, examination, and laboratory investigations. All donors were live related donors. After getting the proper tissue typing and HLA-matching transplant was done and recipients were thoroughly observed for the development of any urological complication in first post-transplant year. Results: Total 8 (16%) subjects developed complications. Urinary leakage was noticed in 3 patients. In one patient leakage stopped spontaneously while in remaining two patients surgical procedure was carried out. Two patients developed uro-sepsis due to intractable UTI. Both were successfully treated with broad spectrum anti biotic. Ureteric stenosis was noticed in 2 subjects. Indwelling JJ stent was placed in one case while remaining case was dealt with uretroneocystostomy. One cases developed Vesico-ureteric reflux. He was treated surgically. Conclusion: Early diagnosis and treatment of urological complication may prevent the further morbidity and decline in graft function. Keywords: pattern, complications, management, post-transplant, first year